Long-term outcome of healthy participants with atrial premature complex: a 15-year follow-up of the NIPPON DATA 90 cohort. - Taku Inohara (Public Library of Science (PLoS), 2013)
Background Atrial premature complexes (APC) are among the most frequently encountered electrocardiographic abnormalities. However, their prognostic value among healthy individuals is unclear. This study aimed to clarify the role of APC in predicting cardiovascular events in a large Japanese community cohort using long-term follow-up data. Methods National Integrated Project for Prospective Observation of Non-communicable Disease And its Trends in the Aged, 1990-2005, (NIPPON DATA 90) was a large cohort study of cardiovascular disease (CVD) in Japan. A total of 7692 otherwise healthy participants with no history of myocardial infarction, stroke, atrial fibrillation, or atrial flutter were enrolled (men, 41.5%; mean age, 52.5 ± 13.7 years). Results A total of 64 (0.8%) participants had at least one beat of APC on screening 12-lead electrocardiogram. During the follow-up of 14.0 ± 2.9 years (total, 107,474 patient-years), 338 deaths occurred due to CVD. The association between APC and CVD outcome was assessed using Cox proportional hazard models. Cox regression analysis revealed that the presence of APC was an independent predictor for CVD deaths (HR: 2.03, 95% CI: 1.12-3.66, P = 0.019). The association of APC on CVD death was more evident in participants with hypertension (P-value for interaction, 0.03). Conclusions APC recorded during the screening electrocardiogram are significantly associated with an increased risk of CVD deaths in a Japanese community-dwelling population and are a strong prognostic factor for hypertensive participants.